Microwave photonics - Lee, Chi H. (Boca Raton : Taylor & Francis Group, 2013)
'In the past decade, we have witnessed world-wide growth of the field of microwave photonics. As microwave photonics deals with interaction between microwaves and optical waves, it leads to new communication systems called fiber-radios which transmit radio frequency signal over optical carriers. Updated to reflect advances in the field, this book provides a systematic introduction by giving a clear overview of many key technologies. In addition a complete revision, the second edition includes new chapters on fiber bragg gratings and applications in microwave photonics and ultrawide band millimeter photonics wireless links'--
Includes bibliographical references (pages 468-475) and index.
Keywords: Optical communications -- Equipment and supplies; Optoelectronics; Microwave communication systems; Photonics